Use of strain, strain rate, tissue velocity imaging, and endothelial function for early detection of cardiovascular involvement in patients with beta-thalassemia - Abhinav Gupta; Aditya Kapoor; Shubha Phadke; Archana Sinha; Shridhar Kashyap; Roopali Khanna; Sudeep Kumar; Naveen Garg; Satyendra Tewari; Pravin Goel (Wolters Kluwer Medknow Publications, 2017)
Background: Global ventricular function often remains normal in patients with beta-thalassemia major. (β-TM) until late. Tissue Doppler and strain imaging may be useful to assess regional myocardial function abnormalities in these patients. Methods: Systolic (Sm), early diastolic (Em), and late diastolic (Am) (Em/Am) myocardial velocities at basal lateral and septal left ventricular (LV) segments, strain (S), and strain rate (SR) in basal and mid LV, right ventricular (RV) and septum were measured in 30 patients (β-TM, 12.4 ± 5.2 years, serum ferritin 2603.1 μg/L) and twenty controls (12.5 ± 5.2 years). Flow-mediated dilatation (FMD) vasodilatation as a measure of endothelial function was also assessed. Results: Patients had significantly higher LV mass index (169.45 ± 61.14 vs. 104.66 ± 24.42; P = 0.009) while global LV Sm and diastolic function was similar to controls. Patients had significantly lower lateral Em velocity, Em (10.12 ± 1.16 vs. 17.9 ± 2.11; P = 0.002), Em/Am ratio (0.811 ± 0.192 vs. 2.06 ± 0.62; P = 0.001) at the basal lateral LV, lower strain values at the basal lateral LV (19.5 ± 4.17 vs. 24.196 ± 1.81; P = 0.002), mid lateral LV (19.07 ± 3.98 vs. 25.56 ± 2.62; P = 0.042), basal septum (17.04 ± 3.44 vs. 25.43 ± 2.53; P = 0.001), and mid septum (20.49 ± 5.34 vs. 24.45 ± 2.20; P = 0.001) as compared to controls. SR at the basal and mid segment of the lateral LV wall and at the basal and mid septum was also significantly lower in patients. SR in basal and mid RV although lower was not significantly different from controls. Patients also had significantly lower FMD (7.57 ± 3.16 vs. 18.08 ± 1.9, P = 0.018) implying endothelial dysfunction. Conclusions: Tissue Doppler, strain and SR imaging are useful to quantify regional myocardial function in asymptomatic α-TM patients with preserved global Sm and diastolic function.